2021
DOI: 10.1101/2021.10.15.464577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Cell-cell Communication in Autistic Brains with Single Cell Transcriptomes

Abstract: Autism spectrum disorder is a neurodevelopmental disorder, affecting 1-2% of children. Studies have revealed genetic and cellular abnormalities in the brains of affected individuals, leading to both regional and distal cell communication deficits. Recent application of single cell technologies, especially single cell transcriptomics, has significantly expanded our understanding of brain cell heterogeneity and further demonstrated that multiple cell types and brain layers or regions are perturbed in autism. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
2
2
0
Order By: Relevance
“…We observed that each factor was associated with different biological functions including axon guidance, cell adhesion, extracellular-matrix-receptor interaction, ERBB signaling, MAPK signaling, among others (Figure 5b). Dysregulation of axon guidance, synaptic processes and MAPK pathway have been previously linked to ASD from differential analysis 55,58 , supporting our observations. Moreover, our results extend to other roles associated with extracellular matrix, focal adhesion of cells, regulation of actin cytoskeleton, and signaling through ErbB receptors, which involves Akt, PI3K, and mTOR pathways, as well as regulation of cell proliferation, migration, motility, differentiation, and apoptosis 59 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that each factor was associated with different biological functions including axon guidance, cell adhesion, extracellular-matrix-receptor interaction, ERBB signaling, MAPK signaling, among others (Figure 5b). Dysregulation of axon guidance, synaptic processes and MAPK pathway have been previously linked to ASD from differential analysis 55,58 , supporting our observations. Moreover, our results extend to other roles associated with extracellular matrix, focal adhesion of cells, regulation of actin cytoskeleton, and signaling through ErbB receptors, which involves Akt, PI3K, and mTOR pathways, as well as regulation of cell proliferation, migration, motility, differentiation, and apoptosis 59 .…”
Section: Resultssupporting
confidence: 90%
“…In our ASD case-study (Figure 5), such analyses included GSEA, clustering, visualization and statistical comparison of factors, and factor-specific analysis of sender-receiver communication networks (Supplementary Figure S9). In the ASD case-study, we found dysregulated CCC directly distinguished ASD patients from controls and was linked with a downregulation of axon guidance, cell adhesion, synaptic processes, and ERBB signaling in cortical neurons and interneurons (Figures 5a,b), consistent with previous evidence 55,58,63,64 . Moveover, accounting for the combinatorial relationship of samples across factors demonstrated additional complex relationships of CCC dysregulation (Figure 5d).…”
Section: Discussionsupporting
confidence: 90%
“…The development of ASD is closely related with neuronneuron communications (64). Synaptic adhesion molecules mediate the communications between presynaptic and postsynaptic neurons and play critical roles in synapse development and plasticity (65).…”
Section: Discussionmentioning
confidence: 99%
“…ASD neuroimaging research examines the brain from a variety of perspectives including brain structure, functional connections, and neurometabolic [8][9][10]. Structural magnetic resonance imaging (sMRI) is a technique for examining the anatomical structure of the brain.…”
Section: Introductionmentioning
confidence: 99%